2019
DOI: 10.1123/jsr.2017-0142
|View full text |Cite
|
Sign up to set email alerts
|

Improving Mobility Performance in Wheelchair Basketball

Abstract: OBJECTIVE: This study aimed to investigate which characteristics of athlete, wheelchair and athlete-wheelchair interface are the best predictors of wheelchair basketball mobility performance. DESIGN: Sixty experienced wheelchair basketball players performed a wheelchair mobility performance test to assess their mobility performance. To determine which variables were the best predictors of mobility performance, forward stepwise linear regression analyses were performed on a set of 33 characteristics, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…42 Similar results were found in wheelchair basketball, in which performance expressed in term of acceleration from standstill, decreased when a deeper sitting position was used. 39,43 In that study, it was also demonstrated that during poling phase, able bodied athletes that assume a deeper sitting position had the trunk more vertical compared to the others, who had an anterior trunk inclination. 39…”
Section: Discussionmentioning
confidence: 88%
“…42 Similar results were found in wheelchair basketball, in which performance expressed in term of acceleration from standstill, decreased when a deeper sitting position was used. 39,43 In that study, it was also demonstrated that during poling phase, able bodied athletes that assume a deeper sitting position had the trunk more vertical compared to the others, who had an anterior trunk inclination. 39…”
Section: Discussionmentioning
confidence: 88%
“…Wheelchair mobility performance closely relates to the athlete–wheelchair interaction, covering two of the main components in wheeled sports (athlete and wheelchair) [ 6 , 7 , 8 ]. By measuring across sports, also the third performance component (sport) is addressed, providing insight in the resemblances and differences across sports.…”
Section: Introductionmentioning
confidence: 99%
“…Anaerobic capacity is deemed to be highly essential in the functionality of the daily life of rehabilitation populations, yet it is only rarely specifically trained [81]. Similarly, the study of motor skill and technique in wheeled mobility would benefit from standardized labmeasurements as presented by Leving et al [82,83], but also by data-driven notions advocated by Van der Slikke et al [74,84,85]. Merging both approaches would benefit our deepened understanding of (athletic) motor skill, motor learning, and performance capacity in the context of disability, classification, and training regimes.…”
Section: From Laboratory To Field Testing In "Mobility Exercise and Spmentioning
confidence: 99%